PROFESSIONALLY SIGNIFICANT ASPECTS OF SPEECH SKILLS IN TEACHING A FOREIGN LANGUAGE - Ashurova Shakhzoda Shavkatovna (Western European Studies, 2024)
In this article we will discuss the professional importance of the speech skills of a foreign language teacher for achieving high results in teaching activities, and also, in contrast to the nature of speech, we will highlight a qualitative measure of the possibilities of implementing a constructive event in a pedagogical situation in which speech skills are characterized by the presence of current uncertainty, when a certain event becomes possible.
Keywords: speech skills; expressiveness; reflexivity